Serum hepatic biochemical activity in two populations of workers exposed to styrene. Issue 2 (1st February 2001) - Brodkin, C A; Moon, J-D; Camp, J; Echeverria, D; Redlich, C A; Willson, R A; Checkoway, H
Abstract : OBJECTIVE: To determine whether hepatic biochemical changes, as measured by routinely available tests indicative of hepatocellular necrosis, cholestasis, or altered hepatic clearance of bilirubin, occur in association with low to moderate exposure to styrene commonly experienced in industrial production. METHODS: Two independent cross sectional studies were performed comparing serum hepatic transaminases (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)), cholestatic enzymes (alkaline phosphatase (AP) and γ glutamyl transpeptidase (GGT)), and bilirubin in ( a ) 47 workers of fibreglass reinforced plastics who were exposed to styrene and ( b ) 21 boat and tank fabricators, with separate referent groups of unexposed workers. Exposure to styrene was assessed in air by dosimetry, and in venous blood by headspace analysis. Hepatic biochemical variables were assessed across strata of exposure to styrene defined as 25 ppm in air, or 0.275 mg/l in blood, adjusting for age, sex, body mass index, and ethanol consumption. RESULTS: A consistent and significant linear trend for increasing direct bilirubin and direct/total bilirubin ratio was found in association with increasing exposure to styrene, by both air and blood monitoring, in both studies. Mean direct bilirubin concentrations increased from 0.05–0.08 mg% in referents to 0.12–0.19 in workers exposed above 25 ppm, with a significant exposure-response trend (p<0.005). Significantly increased direct/total bilirubin ratios, ranging from 0.22 to 0.35 were associated with exposure to styrene (p<0.001), indicating diminished hepatic clearance of conjugated bilirubin. Also, a significant linear association between the hepatic transaminases ALT and AST and exposure to styrene was found in pooled regression analyses, with an increase in AP of about 10 IU/ml in workers exposed above 25 ppm air or 0.275 mg/l blood styrene in pooled analyses from both studies. CONCLUSIONS: The consistent finding of increased direct bilirubin and AP concentrations in these two independent studies provides evidence for diminished hepatic clearance of conjugated bilirubin with associated cholestasis in workers exposed to styrene. The finding of a significant linear association between hepatic transaminase concentrations and exposure to styrene in pooled analyses is consistent with mild hepatic injury and associated metabolic dysfunction.